DETERMINATION OF NATURAL RADIONUCLIDE AND ASSESSMENTS OF HEALTH HAZARDS IN CHICKEN FEEDS AND MEAT CONSUMED IN LAGOS, NIGERIA - Ademola, Augustine Kolapo; Gbadeyanka, Afees (Malaysian Journal of Science, 2021)
Poultry farming is a highly profitable and not capital intensive agricultural project. It is becoming one of the highest investments in agriculture in Nigeria. The proliferation of self -produced feeds by the Farmers with the addition of some minerals to stimulate growth could elevate the levels of radionuclides in feeds. This, therefore, calls for the determination of the health effects from the consumption of these chicken meats and organs. 10 samples of broilers and 30 feed samples (10 each of Starter, Grower, and Finisher feeds used in feeding the chicken) were used; collected from five selected poultry- farms in Lagos State, Nigeria, and analyzed using spectrometry analysis with NaI (Tl). The results obtained showed that concentrations of 40K, 232Th, and 226Ra were 49.0±25.8, 24.9 ±12.2, and 32.9 ±16.2 Bqkg-1 respectively, in chicken meats. In the feeds, their values were below the UNSCEAR recommendation. The annual effective doses in chicken meats and organs were lower than the 70µSv/yr limit. The cancer risk was within the recommended limit, and the internal hazard indices were below unity. The mean values of the transfer coefficient (TC) were also below 1 for 40K, higher than unity for 226Ra in Finisher feeds, and 232Th in Starter feeds. The starter and finisher feeds were moderately contaminated. So, feeding chicken with these feeds may expose the consumers to the danger of over-exposure to 226Ra and 232Th.